(untitled) (Journal of Computational Mathematics, 2000)
Based on a class of functions, which generalize the squared Fischer-Burmeister NCP function and have many desirable properties as the latter function has, we reformulate nonlinear complementarity problem (NCP for short) as an equivalent unconstrained optimization problem, for which we propose a derivative-free descent method in monotone case. We show its global convergence under some mild conditions. If F, the function involved in NCP, is R_0-function, the optimization problems has bounded level sets. A local property of the merit function is discussed. Finally,we report some numerical results.